2018
DOI: 10.1002/cbic.201800230
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Imaging of Salmonella–Host Interactions Using Super‐resolution Correlative Light‐Electron Microscopy of Bioorthogonal Pathogens

Abstract: The imaging of intracellular pathogens inside host cells is complicated by the low resolution and sensitivity of fluorescence microscopy and by the lack of ultrastructural information to visualize the pathogens. Herein, we present a new method to visualize these pathogens during infection that circumvents these problems: by using a metabolic hijacking approach to bioorthogonally label the intracellular pathogen Salmonella Typhimurium and by using these bioorthogonal groups to introduce fluorophores compatible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 62 publications
(29 reference statements)
0
24
0
Order By: Relevance
“…3). 123 The advantage of this approach is that it provides a facile way to image only the proteome of an intracellular pathogen after uptake by a host cell, without any need for further genetic modification of the species. Reacting these proteins with a clickable biotin-or FLAG-tag can also enable the enrichment of these target proteins for mass spec-trometry.…”
Section: Proteome Labeling With Bioorthogonal Amino Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…3). 123 The advantage of this approach is that it provides a facile way to image only the proteome of an intracellular pathogen after uptake by a host cell, without any need for further genetic modification of the species. Reacting these proteins with a clickable biotin-or FLAG-tag can also enable the enrichment of these target proteins for mass spec-trometry.…”
Section: Proteome Labeling With Bioorthogonal Amino Acidsmentioning
confidence: 99%
“…We have also translated the technique to allow super-resolution correlative light-electron microscopy (STORM-CLEM) of pathogens in BMDCs to show the durability of Salmonella bacteria inside the host cell vacuole. 123 Recently, we also combined the BONCAT labeling of the Mtb proteome with the labeling of its PG layer through the use of EDA-labeling with correlative imaging, showing that multiple click reactions can be performed on pathogens simultaneously. We used this approach to assess the heterogeneous effect of various antibiotics on intracellular Mtb (see Fig.…”
Section: Proteome Labeling With Bioorthogonal Amino Acidsmentioning
confidence: 99%
“…SRM-CLEM solves this problem and provides additional single-molecule sensitivity, that allows for visualization of sub-bacterial structures and rare events with low label density. We have previously shown that a combination of bioorthogonal labeling, STORM and TEM (STORM-CLEM) provides an effective tool to study the intracellular behavior of Salmonella enterica serovar Typhimurium (abbreviated here as Salmonella) (van Elsland et al, 2018). The choice of SRM technique stands for achieving the best resolution and using a non-damaging laser power.…”
Section: Figmentioning
confidence: 99%
“…15 However, the specific labeling of fluorescence, necessary to distinguish the molecule of interest in the complex matrix, poses also a disadvantage as the overall structural background (e.g., the ultrastructure of the cell or tissue) is lost. Here correlative imaging can be of great help by combining fluorescence-based methods with techniques able to provide an overall map of the setting of the interactions such as EM, 25 AFM, and soft X-ray microscopy. 26…”
Section: Materials Interactionsmentioning
confidence: 99%